Effect of the Positioning of Metal Centers on a Cavitand in the Ruthenium-Catalyzed N-Alkylation of Amines - Neslihan Şahin; Christophe Gourlaouen; David Sémeril (Molecules)
Two bis-ruthenium(II) complexes, namely N,N′-{5,17-diamino-4(24),6(10),12(16),18(22)-tetramethylenedioxy-2,8,14,20-tetrapentylresorcin[4]arene}-bis-[dichloro-(p-cymene)-ruthenium(II)] (1) and N,N′-{5,11-diamino-4(24),6(10),12(16), 18(22)-tetramethylenedioxy-2,8,14,20-tetrapentylresorcin[4]arene}-bis-[dichloro-(p-cymene)-ruthenium(II)] (2) were synthesized and tested as catalysts in the N-alkylation of primary amines with arylmethyl alcohol using the green “hydrogen borrowing” methodology. The catalytic results were compared with those obtained when the N-{5-amino-4(24),6(10),12(16),18(22)-tetramethylenedioxy-2,8,14,20-tetrapentyl-resorcin[4]arene}-[dichloro-(p-cymene)-ruthenium(II)] (3) complex was employed as catalyst. The rate of the N-alkylation of aniline with benzyl alcohol increased in the order 3 < 1 ≪ 2, which highlights the importance of the relative positioning of the two metal centers on the upper rim of the resorcin[4]arene. Theoretical investigations suggest that the grafting of the two “RuCl2(p-cymene)NH2” moieties on two distal aromatic rings of the cavitand allows a cooperative effect between a ruthenium atom and the coordinated amine of the second metal center.